2019
DOI: 10.9740/mhc.2019.11.359
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder in pregnancy

Abstract: The number of pregnant people affected by the opioid epidemic in the United States continues to rise. The following key aspects of opioid use disorder in pregnancy are explored through the progression of a pregnancy via a patient case: treatment options, treatment decisions, substance use screening, dosing modifications, and other aspects of peripartum care. Many factors affect opioid use disorder treatment choices during pregnancy; however, when a pregnant person is medically eligible for a therapy and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 85 publications
0
11
0
1
Order By: Relevance
“…Infants with prenatal opioid exposure are at risk for premature birth, lower birth weight, and a smaller head circumference (44)(45)(46). These likely result from the influence of maternal opioid/drug use on placental function and nutritional transport, which in turn may lead to fetal growth restriction (47). These neonates often experience postnatal growth issues, believed to result from a withdrawal-induced hypermetabolic state, feeding difficulties, and/or gastrointestinal disturbances (48,49).…”
Section: Nutrition and Growthmentioning
confidence: 99%
“…Infants with prenatal opioid exposure are at risk for premature birth, lower birth weight, and a smaller head circumference (44)(45)(46). These likely result from the influence of maternal opioid/drug use on placental function and nutritional transport, which in turn may lead to fetal growth restriction (47). These neonates often experience postnatal growth issues, believed to result from a withdrawal-induced hypermetabolic state, feeding difficulties, and/or gastrointestinal disturbances (48,49).…”
Section: Nutrition and Growthmentioning
confidence: 99%
“…These medications, approved by the Food and Drug Administration, have been shown to reduce the risk for pregnancy complications that accompany continued drug use or sudden opioid withdrawal, such as fetal distress, preterm births, and underweight babies. 4 Medication-assisted treatment is not without risk, however. It can cause babies to be born with a risk for neonatal abstinence syndrome, 5 a group of conditions that can occur when newborns withdraw from substances they were exposed to in utero.…”
Section: 'Help Them Move Forward'mentioning
confidence: 99%
“…Substance abuse during pregnancy continues to increase in the United States, which has also seen an increase in the rate of women who experience severe health risks during pregnancy and subsequently an increase in the incidence of neonatal abstinence syndrome [ 1 - 5 ]. According to the federal Centers for Disease Control and Prevention (CDC), in 2019, 7% of US women reported that they had used prescription opioids during pregnancy, and one in five of those women reported misusing the drugs while pregnant [ 6 ].…”
Section: Introductionmentioning
confidence: 99%